2015
DOI: 10.1016/j.jmb.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Human CCL18, CCL3, and CCL4 Reveal Molecular Determinants for Quaternary Structures and Sensitivity to Insulin-Degrading Enzyme

Abstract: CC chemokine ligands (CCL) are 8-14 kDa signaling proteins involved in diverse immune functions. While CCLs share similar tertiary structures, oligomerization produces highly diverse quaternary structures that protect chemokines from proteolytic degradation and modulate their functions. CCL18 is closely related to CCL3 and CCL4 with respect to both protein sequence and genomic location, yet CCL18 has distinct biochemical and biophysical properties. Here, we report a crystal structure of human CCL18 and its oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 54 publications
(110 reference statements)
0
25
0
Order By: Relevance
“…2A), nor was it established between monomers from adjacent asymmetric units in the crystal-packing interface. Additionally, the proline in the N-terminus that has been suggested to promote CC chemokine dimerization is absent in CCL21 (23) . Convincingly, Love et al showed through sedimentation equilibrium centrifugation that full-length CCL21 is monomeric (6) .…”
Section: Resultsmentioning
confidence: 99%
“…2A), nor was it established between monomers from adjacent asymmetric units in the crystal-packing interface. Additionally, the proline in the N-terminus that has been suggested to promote CC chemokine dimerization is absent in CCL21 (23) . Convincingly, Love et al showed through sedimentation equilibrium centrifugation that full-length CCL21 is monomeric (6) .…”
Section: Resultsmentioning
confidence: 99%
“…The expression of thioreduxin-tagged CCL5, CCL5(4-68), and CCL3 in Escherichia coli, the removal of thioreduxin-tag by enterokinase or tobacco etch virus (TEV) protease, and the purification of these chemokines by Ni-NTA, source-Q, and heparin columns are done similar to methods described previously (14,47). The octasaccharide heparin MLZ-8f was synthesized as described (35).…”
Section: Methodsmentioning
confidence: 99%
“…An unexplained exception is Aβ 1-40 , the rate of which was increased by approximately twofold by phytic acid. In crystal structures of IDE with bound peptides (28,(35)(36)(37)(38)(39), larger substrates are seen to make contacts at both the active site and the distal site (which mediates activation by peptides). It is possible that activity is not stimulated for large peptides because they themselves activate in a manner similar to polyanions, particularly because their hydrolysis rates are often higher than those for small peptides.…”
Section: Ide Localization To Endosomes Involves the Polyanion-bindingmentioning
confidence: 99%